Oil and gas in a new Libyan era: Conflict and continuity - Barltrop, R (Oxford Institute for Energy Studies, 2019)
This paper analyses the political economy of oil and gas in Libya, examining how the country’s politics affect the oil and gas industry, what has and has not changed since 2011, and the implications and outlook for the future. It begins by briefly reviewing the history of oil and gas development in Libya before 2011. It then proceeds to examine what has happened in the latest, contrasting, period from 2011 to 2018, focusing on how insecurity and political division (in particular the existence of rival governments) have affected the sector, and identifying what the biggest continuities and changes have been. The paper then considers how stability in the NOC and the role of individuals have been, and continue to be, significant for outcomes and prospects, and how competition from local actors seeking oil benefits is intertwined with ongoing dynamics. Finally, the implications for Libya’s future are considered.